Efficiency of Economics of Catfish Growing Business - Fitriani Fitriani; M Zaini (Jurnal Ilmiah ESAI, 2012)
It is important to investigation the economics condition on farming.  It will influence the farmer income and their welfare. This research conducted to examine the economic efficiency on Lele fish growing in Pagelaran District.  The research did by Survey method toward 30 farmer respondent purposively.  Technical efficiency analyzed by Cobb-Douglass production function, while the economic efficiency analyzed by the ratio of marginal production with their price input.  Based on the calculation, it was found out that the ratio of the marginal production toward their price input were unequal 1. There no value represent equal by 1. It means that the Lele fish growing production is on inefficient yet. Achieving the economic efficiency has to support by combining the production factors. So, the farmer’s could increase the production by fixing the combination of input production for getting optimum production and maximum advantage.  Linear programming is such as the appropriate method to solve the input combination for the next focus.  Key words: economic, efficiency, Lele fish growing, marginal production